2011
DOI: 10.1016/j.sder.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

New Agents for Prevention of Ultraviolet-Induced Nonmelanoma Skin Cancer

Abstract: With the incidence of nonmelanoma skin cancer on the rise, current prevention methods, such as the use of sunscreens, have yet to prove adequate to reverse this trend. There has been considerable interest in identifying compounds that will inhibit or reverse the biochemical changes required for skin cancers to develop, either by pharmacologic intervention or by dietary manipulation. By targeting different pathways identified as important in the pathogenesis of nonmelanoma skin cancers, a combination approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 117 publications
1
14
0
2
Order By: Relevance
“…The topical application of photolyase on human skin after exposure to UVB is able to quickly reduce by 55% the formation of CPD [7]. These data support the rational clinical use of topical product containing photolyase in order to reduce the damage to the DNA by exposure to UV [8,9].…”
Section: Introductionsupporting
confidence: 57%
“…The topical application of photolyase on human skin after exposure to UVB is able to quickly reduce by 55% the formation of CPD [7]. These data support the rational clinical use of topical product containing photolyase in order to reduce the damage to the DNA by exposure to UV [8,9].…”
Section: Introductionsupporting
confidence: 57%
“…It has a short photosenisitization period, can treat multiple lesions at the same time, and can give good cosmetic effect. Studies have shown that the depth of penetration for most tissues using 630 nm light is about 1 cm [15,16]. This percutaneous penetration is the most important factor influencing response rates for topical ALA PDT.…”
Section: Photomedicine -Advances In Clinical Practicementioning
confidence: 99%
“…As well, the inhibitory actions of traditional NSAIDs that include aspirin (acetylsalicylic acid) against COX-1 can be crucial problems in clinical pharmacotherapy, such as respiratory-and cutaneous-hypersensitivities and cross-reactivities [26][27][28] . Furthermore, it has been elucidated that COX-2 has key and pivotal roles in (i) induction and proliferation of various types of cancers or tumours in various regions such as colon (colorectal) 29,30 , gastric 31,32 , esophageal 33,34 , skin (non-melanoma/melanoma) [35][36][37] , lung [38][39][40] , liver [41][42][43][44] , pancreatic [45][46][47] , bile duct 48 , gallbladder 48,49 , urinary bladder 50 , breast 51,52 , prostate 53,54 , cervical (uterine cervix) 55,56 , ovarian 57,58 , nasopharyngeal 59 and oral 60 cancers, and in (ii) metastasis of cancers such as lymph node 61,62 , haematogenous 63,64 , gastric 65 , lung 66 , liver [67][68]…”
Section: Introductionmentioning
confidence: 99%
“…In patients with various cancers, adverse prognosis, disease relapse and poor survival rates have been associated with overexpression of COX-2 of cancer/tumour cells/tissues 29-31,36-38,40,44-46,48,51-54,57,58,60-69, 71-75,78-82 . Actually, the cancer/tumour progression mechanisms including initiation, proliferation, invasion, spreading, migration, drug-resistance and metastasis of cancer/tumour cells are caused by (i) COX-2-derived mediators including prostanoids such as PGE 2 , prostaglandin F 2a (PGF 2a ) and thromboxane A 2 (TXA 2 ) and growth factors 37,38,40,43,44,53,54,[60][61][62]65,69,75,79,81,[83][84][85][86][87] , by (ii) DNA oxidative damage resulting from COX-2 activity 54,75,88,89 and/or by (iii) other COX-2-derived signal pathways 42,45,52,57,78 , which are dependent on COX-2 upregulation and activation that result from (i) chronic inflammatory stimuli or carcinogens/tumour-promoters or from (ii) inflammatory-and mitogenic-stimuli in and growth-factors in cancer/tumour cells/ tissues, as mentioned, or from (iii) other promoters/inducers, for example, increased/accumulated ultraviolet (UV) light (UVA, UVB and UVC) exposures 35,36,71,90,91 , radiation exposures 92 , various chronic infections such as Helicobacter pylori (H. pylori) infection 32,…”
Section: Introductionmentioning
confidence: 99%